Survey data on factors influencing participation in towel reuse programs - Efthalia Dimara; Emmanouela Manganari; Dimitris Skuras (Data in Brief, 2017)
This data article provides a data description on all subsamples related to the research article entitled “Don’t change my towels please: Factors influencing participation in towel reuse programs” (E. Dimara, E. Manganari, D. Skuras, 2017) [1]. The dataset was compiled from a field questionnaire survey of 1304 tourists in Greece that captured key demographic, behavioral and psychographic characteristics. The dataset is split into distinct sub-samples that differ depending on whether tourists chose to respond to certain parts of the questionnaire or not. We provide descriptive statistics for the entire sample and all sub-samples as well the questionnaire׳s version in English and the econometric procedures to analyze this complex dataset. This dataset will allow researchers to include the study׳s results in future elaborated meta-analyses and/or gain a better insight to the study׳s major conclusions.